The boosting effect of minoxidil 0.1% when combined with dutasteride 0.01% and microneedling in the treatment of female pattern hair loss - Reham Essam; Heba Selim; Rana Ehab (Journal of the Egyptian Women’s Dermatologic Society)
Background Female pattern hair loss (FPHL) is a disease characterized by progressive hair thinning. Topical minoxidil is an FDA-approved drug for the treatment of androgenetic alopecia. Dutasteride (a 5α-reductase inhibitor) can also be used in a topical form to reduce its systemic side effects. Both agents can be used as mesotherapy after microneedling of the scalp to enhance their potency in the treatment of FPHL. Objective To compare the use of combined minoxidil and dutasteride versus dutasteride alone when applied topically after microneedling of the scalp in the treatment of FPHL. Patients and methods This study included 40 female patients with FPHL. Patients were divided into two groups: one group was treated with combined minoxidil 0.1% and dutasteride 0.01% with microneedling, and the other group received dutasteride 0.01% alone with microneedling. Trichoscopic evaluation was done. Results In a group A, who were treated with combined minoxidil and dutasteride, 4 patients (20%) had excellent improvement, 10 patients (50%) had a good response, 5 patients (25%) had a moderate response, and only 1 patient (5%) had no response, while in a group B, who treated with dutasteride, 1 patient (5%) had excellent improvement, 4 patients (20%) had a good response, 10 patients (50%) had a moderate response, and 5patients(25%) had no response, with a significant difference between both groups (P=0.033. There were the nonsignificant difference between both groups regarding trichoscopic findings before treatment, but after treatment, there was a significant difference between both groups concerning the mean percentage of the follicular unit with one hair and the number of patients who had vellus hairs in the dermoscopic field. Conclusion The combination of minoxidil 0.1% and dutasteride 0.01% after microneedling of the scalp was significantly more effective than dutasteride alone with microneedling for the treatment of FPHL.